(untitled) (International Journal of Medical and Surgical Sciences, 2016)
A successful surgery cannot be done without adequate knowledge of the surgical anatomy, especially in liver trauma, where anatomical knowledge plays a key role when it comes to making quick decisions that will allow saving the life of patients with this pathology in the emergency. Assess liver anatomical knowledge and related structures for conducting emergency surgical approaches mobilization maneuvers and vascular control. A 3-year training program for vascular control maneuvers and liver mobilization, for 11 surgical residents during their second, third and fourth year, while 3 fresh corpses and 20 formolized at 10 % corpses were used. Different maneuvers of liver mobilization and vascular control were performed from the second year onward for three consecutive years. A decrease of 57 % was observed in the time of realization of the maneuvers and recognition of structures in second year residents who conducted this test for three consecutive years, and a decrease of 38 % in second and third year residents who performed it for two consecutive years with similar results. Anatomical knowledge in stage training improves the surgical approach to trauma patients, decreasing the time of realization of the maneuvers and the risk of complications.